Analysis of Corn Farming For Gapoktan Farmers Nagori Sampuran (Case Study: Nagori Bah Sampuran, Jorlang Hataran District, Simalungun Regency) - Wahyunita Sitinjak; Ahmad Muliadi Harahap (Budapest International Research and Critics University, 2022)
The title of the research is